The crucified king : atonement and kingdom in biblical and systematic theology - Treat, Jeremy R., 1980- (Grand Rapids, Michigan : Zondervan, 2014)
The kingdom of God and the atonement are two of the most important themes in all of Scripture. Tragically, theologians have often either set the two at odds or focused on one to the complete neglect of the other. In The Crucified King, Jeremy Treat demonstrates that Scripture presents a mutually enriching relationship between the kingdom and atonement that draws significantly from the story of Israel and culminates in the crucifixion of Christ the king. As Israel's messiah, he holds together the kingdom and the cross by bringing God's reign on earth through his atoning death. The kingdom is the ultimate goal of the cross, and the cross is the means by which the kingdom comes. Jesus' death is not the failure of his messianic ministry, nor simply the prelude to his royal glory, but is the apex of his kingdom mission. The cross is the throne from which he rules and establishes his kingdom. Using a holistic approach that brings together the insights of biblical and systematic theology, this book demonstrates not only that the kingdom and the cross are inseparable, but how they are integrated in Scripture and theology. --From publisher's description.
Introduction : the kingdom and the cross -- Biblical theology. Victory through sacrifice in the Old Testament ; The suffering servant and his kingdom context in Isaiah ; The crucified king in Mark ; The blood of the cross and the kingdom of Christ ; Summary : the kingdom established by the cross -- Systematic theology. Christ : the king on the cross ; Atonement : expansive particularity ; Atonement : reconciling Christus victor and penal substitution ; Kingdom : the cruciform reign of God ; Conclusion : crown of thorns.
Includes bibliographical references (pages 254-284) and index.
Keywords: Jesus Christ -- Crucifixion -- Biblical teaching; Jesus Christ -- Crucifixion; Atonement -- Biblical teaching; Atonement